Aproximación a la cuestión de la semanticidad del signo musical en el teatro contemporáneo - Pascual Rodríguez, Roberto (Revista de Filología Románica, 2006)
The music exists at the theatre from his beginning. However, along the history, the classic comedy, the written drama, has different sense depending on the music. Appia, Meyerhold or Bob Wilson have explained the importance of the music in a staging, an use still polemic nowadays, doubtful, without an unanimous opinion, while the music sounds at the box.